2010
DOI: 10.1038/emboj.2009.407
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan extension by calorie restriction relies on the Sty1 MAP kinase stress pathway

Abstract: Either calorie restriction, loss-of-function of the nutrient-dependent PKA or TOR/SCH9 pathways, or activation of stress defences improves longevity in different eukaryotes. However, the molecular links between glucose depletion, nutrient-dependent pathways and stress responses are unknown. Here, we show that either calorie restriction or inactivation of nutrient-dependent pathways induces lifespan extension in fission yeast, and that such effect is dependent on the activation of the stress-dependent Sty1 mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(171 citation statements)
references
References 68 publications
16
150
1
4
Order By: Relevance
“…On the other hand, Sanchez-Fresneda et al (33) reported that the stress-induced trehalose accumulation is Hog1-independent in Candida albicans. The extension of lifespan in S. pombe is associated with both calorie restriction and increased resistance to oxidative stress (10)(11)(12). Chiming in with a study done on S. cerevisiae by Mahmud et al (34), our results suggest that lifespan extension in S. pombe may not be associated with oxidative stress resistance and trehalose accumulation.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, Sanchez-Fresneda et al (33) reported that the stress-induced trehalose accumulation is Hog1-independent in Candida albicans. The extension of lifespan in S. pombe is associated with both calorie restriction and increased resistance to oxidative stress (10)(11)(12). Chiming in with a study done on S. cerevisiae by Mahmud et al (34), our results suggest that lifespan extension in S. pombe may not be associated with oxidative stress resistance and trehalose accumulation.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, glucose sensing and signaling regulates the increased expression of various stress response genes through the activation of the Atf1p and Pap1p transcription factors in S. pombe (Madrid et al, 2004;Stiefel et al, 2004). The activation of a Sty1 MAP kinase by calorie restriction participates in life span extension, which was shown for the first time by Zuin et al, (2010). In the same study, it was reported that either low-glucose media or activation of the nutrient-dependent Pka1 pathway promoted life span extension in fission yeast, including high respiratory rates, elevated ROS production, activation of the MAP kinase Sty1 pathway and expression of survival genes.…”
Section: Introductionmentioning
confidence: 76%
“…Measurement of Oxygen Consumption-Oxygen consumption of ϳ10 7 cells in 1 ml, collected from anaerobic cultures at an A 600 of 0.5, was measured as described before (35).…”
Section: Methodsmentioning
confidence: 99%